Hyperandrogenism, Elevated 17-Hydroxyprogesterone and Its Urinary Metabolites in a Young Woman with Ovarian Steroid Cell Tumor, Not Otherwise Specified: Case Report and Review of the Literature - Felix C. K. Wong; Angela Z. Chan; W. S. Wong; Angel H. W. Kwan; Tracy S. M. Law; Jacqueline P. W. Chung; Jeffrey S. S. Kwok; Angel O. K. Chan (Case Reports in Endocrinology)
We describe a case of a 24-year-old overweight woman who presented with hirsutism, secondary amenorrhea, clitoromegaly, and symptoms of diabetes mellitus (DM). While a diagnosis of polycystic ovary syndrome (PCOS) with its associated metabolic disturbances was initially considered, serum total testosterone, androstenedione, and 17-hydroxyprogesterone (17-OHP) measured by liquid chromatography tandem mass spectrometry (LC-MS/MS) were significantly increased. As 17-OHP did not increase upon ACTH (Synacthen) stimulation and the urinary steroid profile (USP) was compatible with an ovarian source of 17-OHP excess rather than adrenal, non classical congenital adrenal hyperplasia (NCCAH) was unlikely and an androgen-secreting tumor was suspected. Transabdominal ultrasound revealed the presence of an enlarged right ovary with a polycystic ovary morphology and no discrete mass. Transvaginal ultrasound and [18F]− fluorodeoxyglucose positron emission tomography–computed tomography (FDG PET–CT) enabled the localization of a right ovarian tumor. Laparoscopic right salpingo-oophorectomy was performed and a histological diagnosis of steroid cell tumor, not otherwise specified (SCT–NOS) was made. Hyperandrogenism and menstrual disturbances resolved postoperatively. A literature review revealed that 17-OHP-secreting SCT–NOS may uncommonly show positive responses to ACTH stimulation similar to 21-hydroxylase deficiency. Alternatively, USP might be useful in localizing the source of 17-OHP to the ovaries. Its diagnostic performance should be evaluated in further studies.